Beneficial Plant-Associated Microorganisms From Semiarid Regions and Seasonally Dry Environments: A Review - Bonatelli, Maria Leticia; Lacerda-Júnior, Gileno Vieira; dos Reis Junior, Fábio Bueno; Fernandes-Júnior, Paulo Ivan; Melo, Itamar Soares; Quecine, Maria Carolina (Frontiers in Microbiology, 2021)
Arid regions are apparently low biodiversity environments. However, these environments may host a phylogenetically diverse microbial community associated with plants. Often, its microbial inhabitants are selected to be capable to withstand the stressful setting and improve plant growth under harsh conditions. Thus, plant-associated microbial communities from semi-arid and seasonally dry environments present specifics and general features that will be detailed in the present review. Bacterial community analysis revealed common soil bacterial phyla such as Actinobacteria, Acidobacteria and Proteobacteria. Moreover, cultivable bacteria from semi-arid zones demonstrated different plant growth promotion traits, and were able to improve plant growth in different conditions presented in semi-arid climate, as high salinity and drought. Finally, we also will spotlight the fundamental role of these communities in two important Brazilian’s biomes, Caatinga and Cerrado, and some individual cultivable bacteria that protect plant against abiotic stress highlighting the hydric deficit, as well as new source of several bioproducts such as exopolysaccharides, new inoculants and many others.